Chinese business culture: A study of the source of concepts and how to behave in negotiations with Chinese - Warasiriphong, Chittaworn (Journal of Language and Culture, 2016)
This research aims to study the origin of the concept and how to behave in business negotiations with the Chinese. It is composed in a form of qualitative study by using documents data collection. The study found that the source of concepts about behaving in negotiation with the Chinese was impacted from Confucianism’s Chinese trade concept （儒家） that is called Confucian entrepreneur （儒商文化）, originated from the Five Constant Virtues of Confucianism （五常）, including the concept of righteousness and benefit （义利观）. Confucianism’s Chinese trade has been applied to trade and business negotiation of Chinese businessmen from past to present. A study on how to behave in business negotiations with the Chinese shows three major aspects: language used in business dialogue, ethics in business negotiations and face-saving behavior with the Chinese. Consequently, the mentioned aspects can affect a long-term business relationship. It also relates to how both parties respect and honor each other. In addition, to behave properly in business negotiation with the Chinese is a reflection on the emphasis of the differences among concepts and cultures. Once the negotiation has run properly with an accurate behavior, it would benefit both parties on a success business partnership, together with strong business linkages.